Evaluasi Kesiapan dan Risiko Lingkungan dalam Mendukung Implementasi ISO 14001:2015 pada UPT PAM Belitung - Dwi Nanda Putra; Nurhasanah Nurhasanah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The implementation of an Environmental Management System (EMS) based on ISO 14001:2015 is an approach to improving environmental performance, regulatory compliance, and organizational sustainability. This study aims to evaluate the level of ISO 14001:2015 compliance, assess organizational readiness, and identify environmental risks at the Water Supply Management Unit (UPT PAM) of the Public Works and Spatial Planning Agency (Dinas PUPR) of Belitung Regency. A quantitative descriptive method was employed using ISO 14001:2015 gap analysis, organizational readiness questionnaires, and risk analysis based on a risk matrix. The results indicate a compliance level of 51.72% (moderate category), suggesting that the organization still requires improvements before the full implementation of the Environmental Management System. The organizational readiness assessment yielded an average score of 3.08, indicating a moderately ready condition. Leadership and commitment achieved the highest scores, while human resource competence and operational procedures require further improvement. Risk analysis identified 14 environmental risks, consisting of 1 very high-risk, 3 high-risk, and 10 moderate-risk categories. The primary risk was raw water contamination caused by illegal tin mining activities, with a risk score of 20. Improvement priorities include strengthening EMS documentation, enhancing human resource competence, conducting internal audits and management reviews, and controlling environmental risks to support the implementation of ISO 14001:2015.